Limitation in Fabricating PSf/ZIF-8 Hollow Fiber Membrane for CO2/CH4 Separation - Nik Abdul Hadi Md Nordin; Ahmad Fauzi Ismail; Surya Murali Racha; Ng Be Cheer; Muhammad Roil Bilad; Zulfan Adi Putra; Mohd Dzul Hakim Wirzal (Indonesian Journal of Science and Technology, 2018)
Hollow fiber membrane configuration is way forward in membrane development since it possesses higher packing density and effective surface area per unit module compared to other configuration. Since majority of mixed matrix membrane (MMM) for gas separation reported focuses on flat sheet membrane development, this report aims to address the challenges faced in fabricating hollow fiber MMM. In this study, hollow fiber formulation is fabricated and their MMM using different types of fillers (virgin and modified ZIF-8) are prepared and used as a dispersed phase. The neat hollow fiber membrane shows good results with CO2 permeance of 104.39 GPU and CO2/CH4 selectivity of 29.28, in comparison with reported literature. Upon filler incorporation, the resulted MMMs appear to be diminished in both CO2 permeance and CO2/CH4 selectivity. While using modified ZIF-8, lesser deterioration was shown compared to pure ZIF-8, this phenomenon is likely to occur due to the changes in solution stability which causes notable changes in membrane morphology and performances.